Fuel planning strategies considering operational uncertainties of aerodynamic formation flight - Swaid, Majed; Marks, Tobias; Linke, Florian; Gollnick, Volker (Multidisciplinary Digital Publishing Institute, 2021)
The operational concept of aerodynamic formation flight, also referred to as aircraft wake-surfing for efficiency (AWSE), has high potential in terms of fuel savings and climate impact mitigation. In order to implement this concept, many technological and operational challenges have to be coped with. As the fuel consumption during a mission strongly depends on a successful execution of AWSE, the existing uncertainties regarding flight planning increase. While a conservative fuel planning ensures a follower to complete the mission even in the case of a formation failure, it might result in high amounts of excess fuel and, therefore, additional fuel consumption. In this study, this issue is addressed by the adaptation of flight planning procedures to the requirements of AWSE focusing on fuel planning in particular, considered from the perspective of a designated follower aircraft of a two-aircraft formation. This trade-off is modeled as an n-action two-event decision-making problem. Each of the possible actions is represented by a combination of mission routing and a corresponding diversion airport, taking atmospheric effects (e.g., wind) into account in order to determine the resulting amount of trip fuel. The two events under consideration are a total formation failure in contrast to a complete success. Based on a scenario with a set of double origin destination pairs characterizing the formations and representative weather patterns for the North Atlantic region, each action is analyzed with regard to the expected fuel consumption and expense. Based on a set of assumed formation success probabilities, we find that the proposed method holds a savings potential to reduce the follower’s fuel consumption by <semantics> 4 . 8 % </semantics> and its monetary expenses by <semantics> 1 . 2 % </semantics> compared with a conventional flight planning. In order to gain a monetary profit margin applying this method, the required formation success probability is shown to vary between <semantics> ...